Gomortega keule: micropropagation and germplasm characterization - Munoz-Concha, Diego (2010)
The endangered tree Gomortega keule (Mol.) Baillon belongs to the monotypic family Gomortegaceae and is restricted to a small area in Chile. It produces edible fruit and has other uses. However, there is no initiative aimed at its cultivation, presumably because of its difficult propagation. The literature was reviewed for G. keule. In vitro techniques were assessed as a basis for conservation and future domestication. Zygotic embryos, bud, stem, leaf and petiole explants were used in attempts to establish material in vitro. Cultures for shoot and root production involved evaluation of a range of plant growth regulators, concentrations, supplements and environmental conditions. The use of liquid media for tissue culture of G. keule and somatic embryogenesis was also explored. Contamination was the main hindrance to the establishment of cultures, particularly in explants derived from field-collected shoots. The optimum procedure to establish actively growing cultures of G. keule was the use of zygotic embryos as starting material on semi-solid WP medium with 0.1 mg/l NAA and 1.0 mg/l BAP. Stabilization of the material was a constraint, as tissues often showed hyperhydricity. The optimum conditions for proliferation of shoots of G. keule were on WP medium with 0.1 mg/l NAA, 1.0 mg/l BAP, 8 g/l agar, and 20 g/l sucrose at 18ºC. Phenotypically normal shoots developed on WP medium with 2 g/l activated charcoal. Rooting of those shoots was stimulated with a treatment of 1 week on medium with 20 mg/l IBA. Survival of the plants after acclimatization reached 65% after 8 months. Cultures of compact callus and small embryogenic aggregates showed optimum proliferation in liquid MS medium with 20 g/l sucrose, 0.01 mg/l NAA and 0.1 mg/l 2iP. Somatic embryogenesis was observed from compact calli and from small aggregates when they were transferred onto semi-solid MS medium with 0.01 mg/l NAA and 1.0 mg/l BAP. On the same medium, recurrent somatic embryogenesis was also observed directly from the radicle of zygotic embryos. Somatic embryogenesis was induced in shoots after 6.5 months on semi-solid MS medium supplemented with 1.0 mg/l 2,4-D and 1.0 mg/l 2iP. Embryogenic callus proliferated after cryopreservation, which will complement long-term conservation efforts for G. keule. Chromosomes were observed in cells of embryogenic cultures, suggesting diploidy. Using 9 microsatellites, the genetic fidelity of cultured material and the genetic variation were assessed in natural populations of G. keule. Genetic variation was not detected in two embryogenic genotypes cultured in vitro. The populations of plants showed large genetic variation, indicating that conservation efforts must include southern populations.